Densification mechanism of Ti-Al-Nb alloys pressurelessly sintered from Al-Nb master alloy powder for cost-effective manufacturing - Liu, Xuzhen; Wang, Jun; Li, Yanmo; Li, Shukui; Cai, Qi (Elsevier, 2023)
Pressureless sintering is a cost-effective method to fabricate shaped Ti-Al-Nb alloy components in the aerospace industry. However, the sintering pores in the Ti-Al-Nb alloys led to inferior mechanical properties when using elemental Al powder as the raw material. By completely replacing the Al powder with the Al-Nb master alloy powder, the pores were substantially reduced in the pressurelessly sintered Ti-22Al-17.5Nb (at%) alloy, accompanied by the improvement of the tensile strength. We investigated the densification mechanisms by implementing the isothermal quenching experiments at 500–1200 °C. In the Ti/Al/Nb compact, the pores originated from the melting of Al and the Kirkendall effect at the interfaces of the Ti3Al and Nb particles. The transitions of Ti + 3Al → TiAl3 and α2 → B2 determined the porosity of the sintered alloy. In the Ti/Al-Nb/Nb compact, the Kirkendall pores at the Ti/Al3Nb interfaces were reduced since the diffusion of Al in Ti was retarded. The accelerated diffusion of Nb in Ti3Al suppressed the Kirkendall effect at the Nb/Ti3Al interfaces and promoted the formation of the B2 phase. The ripening of the B2 grains further contributed to the densification of the sintered alloy.
Keywords: Ti-Al-Nb alloy; Pressureless sintering; Powder metallurgy; Phase transition; Densification